IMPLEMENTASI KEBIJAKAN DISIPLIN PEGAWAI DINAS PERHUBUNGAN DAERAH PROPINSI SULAWESI TENGAH - Rusdiah, Rusdiah (Katalogis, 2015)
This study aims at determining the policy enforcement of the Civil Servants’ discipline rules based on Government Regulation No. 53 of 2010 on Discipline of Civil Servants of Transportation Department in Central Sulawesi. The research use descriptive qualitative research methods and the data collection techniques are observations, interviews, and documentations. Seven informants were taken by using purposive sampling. The theory used is the implementation model of George Edward III, communications, resources, disposition and bureaucracy structures. The result of the research indicates that Employee Discipline Policy Implementation in Department of Transportation, Central Sulawesi has not been optimal, with some aspects which influence it, namely: 1). The communication in employee discipline policy in Transportation Department has implemented well and consistent. 2). The resource of employee discipline policy implementation is not adequate in terms of quantity and quality of the employees. 3). Employees’ attitudes in implementing the discipline policy were optimal in comprehension and motivation about employee discipline. 4). Bureaucracy structure in the implementation of employee discipline policy has been adequate through standard operational procedures and good supervision.